Study on coal damage evolution and surface stress field based on infrared radiation temperature. (7th June 2018) - Li, Zhonghui; Cheng, Fuqi; Wei, Yang; Cao, Kang; Zhang, Xin; Zhang, Yongxin; Tian, He; Wang, Xueni
Abstract: To study the evolution of coal damage characteristics based on the infrared radiation temperature (IRT), we analysed the IRT characteristics of coal under uniaxial compression and established a coal damage model according to the relationship between the deformation and maximum IRT (MIRT). In addition, we further deduced a method for imaging the evolution of the surface stress field based on the IRT. The results reveal the following. (1) The MIRT–strain curve corresponds well with the stress–strain curve under loading, and the MIRT can effectively reflect the coal damage. (2) A coal damage evolution model can be established based on the accumulation of the IRT, which can effectively reflect the evolution and development of cracks and the ultimate failure of coal under uniaxial compression. (3) The calculated stresses based on the accumulation of the MIRT can effectively reflect the measured stresses during the destruction of coal. The peak value of the calculated stress–strain curve occurs before the peak of the measured stress–strain curve, providing an innovative approach for the monitoring and early warning of dynamic coal-related disasters. (4) The calculated coal stress field based on the IRT can effectively reflect the compressive deformation of coal, and the calculated stress field corresponds well with localized failure. These results provide a new non-contact measurement method for determining the surface stress field distribution of coal using IRT technology.